The Effect of the COVID-19 Pandemic and the Establishment of a Ronald McDonald House on Skin-to-Skin Times in the Neonatal Intensive Care Unit: A Retrospective Study - Stephanie Schaible; Edda Hofstätter; Wanda Lauth; Martin Wald (Children, 2025)
Objectives: Kangaroo care is vital for the development of premature and low-birthweight infants. However, detailed data on skin-to-skin times, especially for extremely preterm infants in NICUs, is lacking. This study quantifies skin-to-skin times for these infants at the neonatology department in Salzburg, considering factors like the COVID-19 pandemic, the opening of Ronald McDonald House, and sibling presence. Methods: We retrospectively analyzed data from the first eight weeks of life of 93 extremely preterm infants (<28 gestational weeks, <1500 g birth weight) treated at the Salzburg NICU from 2019 to 2023. Skin-to-skin times were recorded to the minute. Results: The mean value skin-to-skin time per visiting day was 241 min (±83), skin-to-skin was performed on 79.0% (±16.8) of the days of stay examined. During the pandemic, skin-to-skin care was performed on 64% of visit days, after the pandemic on 91% (p < 0.001). Before the Ronald McDonald House opened, the skin-to-skin time per visiting day was 215 min (±57.9), afterwards it was 273 min (±97) (p = 0.001). For Primipara the Kangaroo-Care time per day of visit was 257 min (±93), for Multipara 217 min (±52) (p = 0.043). Conclusions: Skin-to-skin is crucial for extremely premature infants and can be implemented for many hours a day. It is an integral part of parent-child interaction in a neonatal intensive care unit. External factors such as infrastructure, pandemic restrictions or siblings have a significant impact on skin-to-skin.